Near‐Net Shape Hot Isostatic Pressing: Microstructural Analysis and Hardness Evolution at a Steel–Nickel Alloy Interface. Issue 11 (12th February 2022) - Yang, Lebiao; Xie, Yin; Ren, Xiaona; Cai, Chao; Xue, Pengju; Shi, Yusheng; Ge, Changchun
Abstract: For near‐net shape hot isostatic pressing (HIP) process, the interaction between capsules and consolidating powders at a high pressure and temperature leads to a strong interfacial element diffusion, which is harmful to the surface microstructure and mechanical properties of components. The effects of iron and carbon, in SS400 steel capsules, on the surface microstructure and mechanical properties of the FGH4096M superalloy during HIP are investigated. Results show that the interfacial difussion between the SS400 steel and FGH4096M is divided into three zones: ferrite‐martensite‐austenite mixture zone (≈32.3 µm), Fe‐rich Ni‐Fe‐based superalloy zone (≈27.5 µm), and Ni‐rich Ni‐Fe‐based superalloy zone (≈34.8 µm). The γ′ phase starts to be formed when the mass fraction of iron is below ≈27.2%. The γ′ morphology changes from fine sphere to cuboidal and butterfly‐like shapes as the mass fraction of iron is decreased successively. There is no obvious carbon diffusion around the interface due to a low carbon concentration in the capsule. The Vickers microhardness profile shows an increase, then a decrease, and eventually becomes stable at 425HV. Based on the above conclusions, an understanding of the Fe and C diffusion mechanism at the interface and its extension toward the FGH4096M side is achieved. Abstract : A variety of characterization techniques are used to conduct in‐depth research on the interface between the FGH4096M superalloy and SS400 low‐carbon steel. The diffusion behavior of Fe and C from SS400 low‐carbon steel to FGH4096M superalloy during hot isostatic pressing (HIP) is revealed. The relationship among the diffusion distance of iron, γ′ phase, and Vickers microhardness is established.